Fertilization by coral-dwelling fish promotes coral growth but can exacerbate bleaching response. (21st May 2022) - Detmer, A. Raine; Cunning, Ross; Pfab, Ferdinand; Brown, Alexandra L.; Stier, Adrian C.; Nisbet, Roger M.; Moeller, Holly V.
Highlights: Fish excretion is incorporated into a coral-algal dynamic energy budget model. Fish presence enhances coral growth in low flow, low nitrogen environments. Fish can increase risk of bleaching in corals experiencing photo-oxidative stress. Fish effects are driven by impacts of nitrogen on symbiont density and carbon sharing. Abstract: Many corals form close associations with a diverse assortment of coral-dwelling fishes and other fauna. As coral reefs around the world are increasingly threatened by mass bleaching events, it is important to understand how these biotic interactions influence corals' susceptibility to bleaching. We used dynamic energy budget modeling to explore how nitrogen excreted by coral-dwelling fish affects the physiological performance of host corals. In our model, fish presence influenced the functioning of the coral-Symbiodiniaceae symbiosis by altering nitrogen availability, and the magnitude and sign of these effects depended on environmental conditions. Although our model predicted that fish-derived nitrogen can promote coral growth, the relationship between fish presence and coral tolerance of photo-oxidative stress was non-linear. Fish excretions supported denser symbiont populations that provided protection from incident light through self-shading. However, these symbionts also used more of their photosynthetic products for their own growth, rather than sharing with the coral host, putting the coral holobiont at a higher risk of becoming carbon-limited and bleaching. The balance between the benefits of increased symbiont shading and costs of reduced carbon sharing depended on environmental conditions. Thus, while there were some scenarios under which fish presence increased corals' tolerance of light stress, fish could also exacerbate bleaching and slow or prevent subsequent recovery. We discuss how the contrast between the potentially harmful effects of fish predicted by our model and results of empirical studies may relate to key model assumptions that warrant further investigation. Overall, this study provides a foundation for future work on how coral-associated fauna influence the bioenergetics of their host corals, which in turn has implications for how these corals respond to bleaching-inducing stressors.